Differences in physician opinions about controversial issues surrounding contralateral prophylactic mastectomy (CPM): A survey of physicians from accredited breast centers in the United States. (11th March 2020) - Yao, Katharine; Bleicher, Richard; Moran, Meena; Chang, Cecilia; Dietz, Jill; Stearns, Vered; Connolly, James; Sarantou, Terry; Kurtzman, Scott; ,
Abstract: Background: Indications and insurance coverage for contralateral prophylactic mastectomy (CPM) and CPM as a quality measure are controversial. Few studies have examined physician opinions on these issues. Methods: A cross‐sectional survey of multi‐specialty physicians at the National Accreditation Program for Breast Centers from 2017‐2018 examined opinions on insurance coverage for CPM, CPM as a quality measure, and indications for CPM. A multivariate logistic regression was used to assess physician and facility factors associated with likelihood to recommend CPM. Results: Of 2412 physicians, 1226 responded from 382 facilities for a physician response rate of 50.8%. There were 300 (24.5%) medical oncologists, 316 (25.8%) radiation oncologists, 248 (20.2%) plastic surgeons, and 322 (26.3%) oncologic or general surgeons. Three hundred and ninety‐eight (37%) physicians favor insurance coverage for all patients and 520 (46.6%) for patients at average CBC risk. Four hundred and fifty (40%) of all physicians felt physician specific rates of CPM should be a hospital quality measure. BRCA deleterious mutation carrier status was the most common indication to recommend CPM (n = 1043; 92%) and 684 (60.2%) physicians discourage CPM for average contralateral risk (CBC) patients. After adjusting for physician and facility factors, the only significant predictor of higher likelihood to recommend CPM for average CBC risk patients were plastics surgeons (OR = 8.3 (95%CI 2.4‐29.1)) P  = .0009). Conclusion: There is consensus among physicians on the most appropriate indication for CPM but opinions vary on CPM as a quality measure and insurance coverage for CPM. These findings can help guide discussions on CPM among a multidisciplinary team of physicians. Abstract : A survey of over 1200 physicians working at accredited breast centers in the United States showed there is consensus among physicians on the most appropriate indication for contralateral prophylactic mastectomy (CPM) but opinions vary on CPM as a quality measure and insurance coverage for CPM.